Moral contagion : black Atlantic sailors, citizenship, and diplomacy in antebellum America / Michael A. Schoeppner. - Schoeppner, Michael A. (Studies in legal history., 2019)
Between 1822 and 1857, eight Southern states barred the ingress of all free black maritime workers. According to lawmakers, they carried a 'moral contagion' of abolitionism and black autonomy that could be transmitted to local slaves. Those seamen who arrived in Southern ports in violation of the laws faced incarceration, corporal punishment, an incipient form of convict leasing, and even punitive enslavement. The sailors, their captains, abolitionists, and British diplomatic agents protested this treatment. They wrote letters, published tracts, cajoled elected officials, pleaded with Southern officials, and litigated in state and federal courts. By deploying a progressive and sweeping notion of national citizenship - one that guaranteed a number of rights against state regulation - they exposed the ambiguity and potential power of national citizenship as a legal category. Ultimately, the Fourteenth Amendment recognized the robust understanding of citizenship championed by Antebellum free people of color, by people afflicted with 'moral contagion'.